The tangle of colonial modernity: Hong Kong as a distinct linguistic and conceptual space within the global common law - Christopher Hutton (Law Text Culture, 2014)
Hong Kong, or more formally, the Hong Kong Special Administrative Region (SAR), is a common law jurisdiction within the People’s Republic of China (PRC). Hong Kong was officially a British colony from 1843 to 1997, although colonial rule began in practice in 1841. Post-1997 Hong Kong is unusual in that it is a common law jurisdiction within a civil law state, the legal system of which was set up initially on the Soviet model. The People’s Republic of China is a unitary state under one party rule, and no power can be permanently ceded from the centre. Hong Kong is therefore a zone of discretionary exception created under the ‘one country, two systems’ policy, albeit one buttressed by an international agreement, the Sino-British Joint Declaration of 1984, and formalised in the Basic Law. A striking feature of this constitutional arrangement is that it is time-bound. The ‘high degree of autonomy’ promised to Hong Kong expires on June 30, 2047, with the subsequent special status of Hong Kong, if any, yet to be determined.